Insight into ultrasound-assisted phosphorylation on the structural and emulsifying properties of goose liver protein. (30th March 2022) - Hu, Yangyang; Wu, Zhen; Sun, Yangying; Cao, Jinxuan; He, Jun; Dang, Yali; Pan, Daodong; Zhou, Changyu
Graphical abstract: Highlights: Ultrasound-assisted phosphorylation enhanced conjugation of phosphate group to GLP. Phosphorylation changed conformation and increased solubility, zeta potential of GLP. The enhanced phosphorylation degree was responsible for EAI and ESI improvement of GLP. Abstract: The aim of this study was to elucidate the effect of ultrasound-assisted phosphorylation on the structural and emulsifying properties of goose liver protein (GLP), and GLP underwent different treatments (native (GLP-N), only ultrasound (UGLP), only phosphorylation (GLP-STP) and ultrasound-assisted phosphorylation (UGLP-STP)). UGLP-STP showed the highest phosphorylation degree of GLP among four groups; The FT-IR spectrum confirmed the phosphate group covalently attached to GLP in UGLP-STP. The highest hydrophobic capability and solubility were exhibited in UGLP-STP, resulting from the transformation of α-helix and β-turn into β-sheet and random coil. The treatment of UGLP-STP showed significantly higher values in emulsifying activity (32.24 ± 0.27 m 2 /g) and emulsifying stability (103.59 ± 2.40%) compared with other treatments. Confocal laser scanning microscopy suggested that UGLP-STP showed largest uniformity of particle distribution and smallest size than other groups. These results implied that ultrasonic-assisted phosphorylation showed a great improvement in emulsifying properties of goose liver protein.